1986
DOI: 10.1093/ajcn/44.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Food iron and lead absorption in humans

Abstract: Food iron and lead absorption were measured simultaneously in 28 subjects by extrinsically labeling three consecutive meals with the radioactive tracers, iron 59-sulfate and lead 203-chloride. Absorption was measured directly in all subjects by whole-body counting and indirectly in 15 subjects by assessing subsequent levels of tracer in blood. Iron status of the subjects ranged from iron deficient to replete, thus providing a wide range of iron absorption. Statistically significant positive correlations were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 21 publications
2
27
0
2
Order By: Relevance
“…Because heavier women are unlikely to gain as much weight and arm circumference as smaller ones, gain becomes an especially Our analysis of maternal diet provides new information on nutrient-lead interactions because it pertains to the transfer of lead from mother to fetus whereas most published research examines relationships of dietary intake and lead levels in either adults or children. In the APILS sample, higher maternal intakes of iron are associated with lower neonatal lead levels, a finding consistent with results from both experimental animal studies (Barton et al 1978;Crowe and Morgan 1996;Hamilton 1978;Hashmi et al 1989aHashmi et al , 1989bKlauder and Petering 1975;Mahaffey-Six and Goyer 1972;Ragan 1977;Shukla et al 1990;Singh et al 1991;Suzuki and Yoshida 1979) and human studies (Cheng et al 1998;Hammad et al 1996;Mahaffey and Annest 1986;Markowitz et al 1990;Szold 1974;Watson et al 1980Watson et al , 1986Wright et al 1999;Yip et al 1981;Yip and Dallman 1984) that have shown negative associations between iron intake or iron status and blood lead levels. Despite this negative relationship between maternal dietary iron and infant lead levels, we found no significant association between mother's iron stores (serum ferritin) and newborn's blood lead levels in bivariate or multivariate analysis (data not shown), mirroring the results of Milman and colleagues (1988).…”
Section: Discussionsupporting
confidence: 82%
“…Because heavier women are unlikely to gain as much weight and arm circumference as smaller ones, gain becomes an especially Our analysis of maternal diet provides new information on nutrient-lead interactions because it pertains to the transfer of lead from mother to fetus whereas most published research examines relationships of dietary intake and lead levels in either adults or children. In the APILS sample, higher maternal intakes of iron are associated with lower neonatal lead levels, a finding consistent with results from both experimental animal studies (Barton et al 1978;Crowe and Morgan 1996;Hamilton 1978;Hashmi et al 1989aHashmi et al , 1989bKlauder and Petering 1975;Mahaffey-Six and Goyer 1972;Ragan 1977;Shukla et al 1990;Singh et al 1991;Suzuki and Yoshida 1979) and human studies (Cheng et al 1998;Hammad et al 1996;Mahaffey and Annest 1986;Markowitz et al 1990;Szold 1974;Watson et al 1980Watson et al , 1986Wright et al 1999;Yip et al 1981;Yip and Dallman 1984) that have shown negative associations between iron intake or iron status and blood lead levels. Despite this negative relationship between maternal dietary iron and infant lead levels, we found no significant association between mother's iron stores (serum ferritin) and newborn's blood lead levels in bivariate or multivariate analysis (data not shown), mirroring the results of Milman and colleagues (1988).…”
Section: Discussionsupporting
confidence: 82%
“…Results of both animal and human studies have confirmed that IDA increases intestinal lead absorption. [15][16][17] A reasonably wellestablished epidemiologic association has been made between IDA and increased lead concentrations. 18 Thus, primary prevention of IDA could also serve as primary prevention of lead poisoning.…”
Section: Prevalence Of Id and Idamentioning
confidence: 99%
“…high iron absorption due to low iron status is accompanied by high lead absorption (14). Iron absorption is impaired by a concomitant intake of calcium (11).…”
Section: Discussionmentioning
confidence: 99%